Proyeksi Penerimaan Pajak Bumi dan Bangunan Pedesaan Perkotaan pada Badan Pengelolaan Keuangan dan Aset Daerah Kota Bengkulu - Azuwandri; Gustini; Mulyadi (Business Perspective Journal, 2024)
The aim of this study is to know the tax revenue projection of land and building sector rural and urban during 2021-2023 at Finance and Asset Management Agency Bengkulu City. This study uses quantitative method. The data used in this study is secondary data, which includes data report on the realization budget of land tax and buildings sector rural and urban 2016-2020. Documentation is used as technique of data collecting method. Analysis method used in this research is trends analysis method of least square. Based on the result, it can be concluded that the realization growth of Land and Building Sector Rural and Urban Tax Revenue in 2016-2020 has fluctuated where in 2016 its revenue amounted to RP 10.810.375.613, in 2017 increased so that Rp16.778.098.917, and in 2018 decreased to Rp 6.968.054.346, in 2019 increased to Rp 7.637.001.135, then in 2020 increased again to Rp 8.502.110.732 resulting in the projection trends of tax revenues of land and building sector rural and urban in Bengkulu City 2021-2023 respectively as follows: in 2021 amounting to Rp 26.186.120.521, 2022 amounting to Rp 29.107.242.309, in 2023 amounting to Rp 32.028.364.096 Keywords: Tax of Land and Building, Sector Rural and Urban, BPKAD